Dietary protein improves flesh quality by enhancing antioxidant ability via the NF-E2-related factor 2/Kelch-like ECH-associated protein 1 signaling pathway in softshell turtle (Pelodiscus sinensis) - Kou, Hongyan; Hu, Junru; Liu, Xueting; Zhao, Lijuan; Zhang, Kai; Pan, Xunbin; Wang, Anli; Miao, Yutao; Lin, Li (Frontiers in Nutrition, 2022)
An 8-week feeding trial was performed to assess the influence of a gradient of protein levels (14.38–45.23%) on flesh quality, skin color, amino acid profile, collagen, antioxidant capability, and antioxidant-related signaling molecule expression of the softshell turtle (Pelodiscus sinensis). Hardness, gumminess, chewiness, and yellowness values in the plastron and carapace, along with collagen, superoxide dismutase, catalase, total antioxidant capacity, and glutathione peroxidase, all improved with elevating dietary protein up to 26.19%, after which they leveled off. Additionally, total amino acids, flavor amino acids, essential amino acids, and non-essential amino acids in the muscle, as well as the expression of copper/zinc superoxide dismutase, glutathione peroxidase, catalase, manganese superoxide dismutase, NF-E2-related factor 2 were all enhanced by increasing the dietary protein level but not changed by higher protein levels. When dietary protein levels were less than 26.19%, the mRNA expression of Kelch-like ECH-associated protein 1, malondialdehyde, and redness values in the carapace and plastron were reduced, as was the lightness values of the carapace, all of which plateaued at higher protein levels. Using catalase activity and malondialdehyde as the indicators and applying a broken-line analysis, the optimal dietary protein level for P. sinensis was inferred to be 26.07 and 26.06% protein, respectively. In summary, an optimal protein input improved turtle flesh quality by strengthening antioxidant capacity in muscle tissue and by regulating the expression of antioxidant-related enzymes via the Nrf2/keap1 signaling pathway.